The Construction of Genetic Map of Faba Bean (Viciafaba L.) Using RAPD Markers - Memen Surahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
Fifty seven individuals of recombinant inbred lines (RlLs) of faba bean (Viciaf aba L.) descended from the cross between 34Morocco x Kristal125 have been analyzed for RAPD markers. A total of 77 markers were assayed segregating in the 57 Rl lines and grouped into 14 linkage groups, with total length of 973.2 cM Key words: Vicia faba, Recombinant in bred line, RAPDs, Linkage groups